Analysis of reactive oxygen species and antioxidant defenses in complex I deficient patients revealed a specific increase in superoxide dismutase activity - Wani, Aijaz A.; Rangrez, Ashraf Y.; Kumar, Himanshu; Bapat, Sharmila A.; Suresh, C. G.; Barnabas, Shama; Patole, Milind S.; Shouche, Yogesh (Free Radical Research, 2008)
The mechanism of free radical production by complex I deficiency is ill-defined, although it is of significant contemporary interest. This study studied the ROS production and antioxidant defenses in children with mitochondrial NADH dehydrogenase deficiency. ROS production has remained significantly elevated in patients compared to controls. The expression of all antioxidant enzymes significantly increased at mRNA level. However, the enzyme activities did not correlate with high mRNA or protein expression. Only the activity of superoxide dismutase (SOD) was found to correlate with higher mRNA expression in patient derived cell lines. The activities of the enzymes such as glutathione peroxidase (GPx), Catalase (CAT) and glutathione-S-transferase (GST) were significantly reduced in patients (p < 0.05 or p < 0.01). Glutathione reductase (GR) activity and intracellular glutathione (GSH) levels were not changed. Decreased enzyme activities could be due to post-translational or oxidative modification of ROS scavenging enzymes. The information on the status of ROS and marking the alteration of ROS scavenging enzymes in peripheral lymphocytes or lymphoblast cell lines will provide a better way to design antioxidant therapies for such disorders.
Keywords: antioxidant enzymes; mitochondrial complex I; mitochondrial myopathies; Reactive Oxygen Species (ROS)